Axial stiffness for large-scale ball slewing rings with four-point contact - Slavomir Hrcek; Robert Kohar; Jan Steininger (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
This article deals with the design of slewing rings (slewing bearings). A fully parametric, 3D virtual model of a ball slewing ring with four-point contact was created in the PTC/Creo Parametric CAD system. This model was subsequently used for finite-element analysis using Ansys/Workbench CAE software. The purpose of the FEM analysis was to determine the axial stiffness characteristics. Results of FEM analysis were experimentally verified using a test bench. At the end of the article, we present the nomograms of the deformation constant for different pitch diameters, rolling element diameters and contact angles.